Institutional Arrangements for the Creative Economy and Empowerment of Business Actors: A Study in Malang City - Azna Abrory Wardana; Lintang Edityastono (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study examines the institutional arrangements governing the creative economy in Malang City and evaluates their implications for the empowerment and performance of creative business actors. Nationally, the creative economy is supported by Law No. 24/2019 and Government Regulation No. 24/2022, which mandate local governments to provide infrastructure, financing schemes, and ecosystem facilitation. Malang City has adopted this framework through its Creative Economy Development Action Plan 2023–2027 and the establishment of the Malang Creative Center (MCC) as a collaborative hub for 17 creative subsectors. Employing a qualitative policy case study and a socio-legal approach, this research analyzes regulatory documents and triangulates them with semi-structured interviews involving government officials, MCC managers, and creative actors. Findings show that Malang possesses a relatively advanced normative framework, yet institutional implementation remains fragmented. Overlapping mandates, weak cross-agency coordination, and unclear institutional entry points hinder effective service delivery. MCC has become the primary provider of training, mentoring, and promotional facilities, and actors engaged in these programs report improved networks, digital capabilities, and business development. However, benefits remain uneven, with digitally connected and campus-based communities receiving more support than peripheral subsectors such as home-based crafts, small culinary businesses, and traditional fashion. The study also identifies a direct relationship between institutional quality and business strategy. Actors with stronger institutional linkages tend to adopt innovative business models, expand markets—including through digital platforms—and pursue formal financing opportunities. Conversely, limited institutional exposure results in localized, traditional business strategies. Theoretically, the study highlights how institutional arrangements bridge legal logic and business logic, reinforcing the relevance of institutional theory, public service management, and empowerment frameworks. Practically, the findings call for clearer division of roles, strengthened service hubs, inclusive empowerment programs, and integrated digital literacy and financing initiatives to enhance creative economy governance in Malang City.